AN UNUSUAL LABIAL HEMATOMA WITHOUT ASSOCIATED FRACTURE FOLLOWING TRAUMATIC INJURY TO CHIN – A CASE REPORT WITH MINI REVIEW - Kuthiala, Parnika; Bhanot, Rishabh; Shoyab Khan, Mohammad; Grufan, Khalid; Iqbal, Mohammad Shahid; Tabbasum, Aisha (International Journal of Psychosocial Rehabilitation, 2020)
Hematoma if untreated may possibly lead to poor wound healing, localized infection, and skin necrosis. Usually, hematoma following maxillofacial injury is associated with fracture of the facial bones. We report a case in which the patient sustained a blunt injury to the chin that resulted in a massive expanding hematoma of the chin without any associated facial bone fracture. The hematoma was evacuated under local anesthesia and periodic follow up of the patient revealed satisfactory healing of the traumatized area. This case report highlights the fact that a vigilant clinical & radiological examination coupled with thorough hematological investigations is essential in patients presenting with posttraumatic hematoma following blunt trauma.